A DIGITAL MARKETING STRATEGY USING SOCIAL MEDIA MARKETING TO INCREASE CONSUMER PURCHASE DECISIONS MEDIATED BY BRAND PERCEPTION - Hannan, Sufrin; Piramita, Santi; Purba, Jan Horas Vervady (Jurnal Aplikasi Manajemen, 2023)
Improving customer impressions of non-subsidized mortgages is one of the challenges facing banks today, and the use of digital marketing media has become necessary to win the competition. This study attempts to examine the roles of brand perception in mediating the interactions between social media marketing and customer purchase decisions in the non-subsidized mortgage setting since consumer perception is still a problem in non-subsidized mortgages in Indonesia. Three hundred twenty participants from non-subsidized mortgage debtors who have had new credit agreements for more than three months and who follow Bank XYZ on Instagram were used in this study. PLS-SEM, or partial least square structural equation modeling, was used in this study's data analysis. According to the findings, brand perception significantly and positively mediates the influence of social media marketing on customer purchasing decisions. The study's findings suggest that Bank XYZ has to improve its social media marketing approach, focusing on producing engaging, interactive, and educational content for users. Building a brand relationship with customers is extremely important for improving brand perception. Consumers will find it simpler to use a mortgage at Bank XYZ because of the perception connected to their minds.